Retrospective comparative survival analysis of ablation plus systemic therapy versus systemic therapy alone for breast cancer liver metastases, stratified by extrahepatic metastases status - Xuxiazi Zou; Hong-Liang Zou; Xuan Luo; Xu-Wei Chen; Wei-Ling Huang; Chao Zhang; Ge Ren; Jin-Hua Huang; Xue Han; Yi-Quan Jiang (Breast)
Background: Current decision-making for the treatment of breast cancer liver metastases (BCLM) using ablation lacks strong evidence, especially for patients combined with extrahepatic metastases. Purpose: To assess whether ablation plus systemic therapy (AS) improves survival outcomes in patients with BCLM compared to systemic therapy alone. Materials and methods: This retrospective study analyzed patients with BCLM who received either AS or systemic therapy alone. Propensity score matching (PSM) and survival analysis were performed, taking into account factors like the characteristics of primary breast cancer, liver metastases and systemic therapies received. Results: The study included 1021 female patients, with a median follow-up of 39.6 months. Of these patients, 132 underwent AS and 836 received systemic therapy alone. After PSM, among patients with BCLM (≤3 tumors, each ≤3 cm), the median overall survival (OS) for those treated with AS or systemic therapy alone was 65.5 and 40.4 months, respectively (HR = 0.48, p = .003); in the subset of patients with extrahepatic metastases, the median OS for those treated with AS and systemic therapy alone was 46.4 and 40.8 months, respectively (HR = 0.58, p = .047). Among patients with >3 cm or >3 lesions, the median OS for those treated with AS or systemic therapy alone was 45.2 and 29 months, respectively (HR = 0.67, p = .084). Conclusions: Among patients with BCLM (≤3 tumors, each ≤3 cm), AS provide longer survival compared to systemic therapy alone, even with extrahepatic metastases. For patients with larger or more numerous metastases (>3 cm or >3 lesions), AS may provide survival benefit, but further validation is needed.